Implementasi Sewa Jasa Endorsment Dalam Meningkatkan Penjualan Produk Dalam Perspektif Hukum Ekonomi Islam - Hardiati, Neni; Latifah, Ida; F, Fitriani (Media Hukum Indonesia (MHI), 2024)
This study aims to analyze the Islamic economic law review of the implementation of endorsement service rental as one of the marketing strategies in increasing product sales. Endorsement is a form of cooperation between a company or product owner and an influential individual, such as a celebrity or influencer, to promote the product to a wider audience. This study uses a qualitative method with a literature study approach to understand how Islamic economic law views the practice of endorsement. Based on the analysis conducted, the implementation of endorsement service rental from an Islamic legal perspective must meet the requirements in accordance with sharia principles, such as a clear contract between the two parties, no elements of gharar (uncertainty), usury, and maisir (gambling). In addition, the advertised product must be halal and in accordance with sharia ethics. The results of the study indicate that endorsement can be a legitimate and effective strategy in increasing product sales as long as it meets the basic principles of Islamic economic law. The conclusion of this study is that endorsement service rental is a form of transaction that is permitted in Islamic law as long as the contract used is clear, the product being promoted is halal, and there is no element of fraud or uncertainty in the agreement.